Effects of ω-3 PUFA-enriched diet on growth parameters in a syngenic murine model of breast adenocarcinoma: a possible role for estrogen receptor alpha - Vara Messler, Marianela (2013)
Fil: Vara Messler, Marianela. Universidad Nacional de Córdoba. Facultad de Ciencias Médicas. Instituto de Biología Celular; Argentina.